"A Critical and comparative analysis of the public interest case law jurisprudence of the competition tribunal of South Africa on large and notifiable mergers, since the enactment of the competition act no.89 of 1998(as amended)". - Zwane, Bhangase, Patrick, Mzabalazo (University of the Witwatersrand, Johannesburg, 2007)
The Competition Act no.89 of 1998 coupled with its amendments ushered in a new era in the competition analysis and merger approval process in South Africa. This research paper's purpose is to intimately explore the emergent doctrine of "public interest" institutionalized in this new dispensation of competition legislation. In particular this report places under the spotlight the treatment of public issues in case law jurisprudence as developed in the consideration and determination of large and notifiable mergers under the auspices of the competition tribunal of the Republic of South Africa since the inception of the said new legislative order. The efficacy of the determination of socio-political issues and pure competitive efficiency issues separately but under and by the same entity are also examined. The contrast between the South African approach to the application of the doctrine of the public interest and that of some other competition jurisdictions abroad is also explored.
Theses
Keywords: Consolidation and merger of corporations; Law and legislation -- South Africa; Antitrust law -- South Africa